PENGGUNAAN APLIKASI QUIZIZZ DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 3 SDN 64 AMBON - Aitonam, Claudia; Serpara, Henderika; Wenno, Eldaa Crystle (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This study aims to examine the effect of using the Quizizz application in increasing the learning motivation of grade 3 students at SDN 64 Ambon. The research method used is participatory observation. The data obtained is data collected through direct observation of student activities during the learning process using the Quizizz application, student interviews, and documentation obtained during the learning process. The results of the study indicate that the use of the Quizizz application in the learning process can increase student learning motivation, marked by increased active participation, enthusiasm, and self-confidence during the learning process. Interactive quizzes provided by Quizizz or those prepared by teachers make learning more interesting and challenging, so that students are more motivated to achieve better learning outcomes.